A Microwave VNA for Biomedical In-line Concentration Measurements - Hofmann, Maximilian; Bauch, Andreas; Weigel, Robert; Fischer, Georg; Kissinger, Dietmar (BioWireless Conference, 2013)
This paper presents a microwave (MW) test-set designed for biomedical in-line concentration measurements. The demonstrator consists of a commercial voltage controlled oscillator (VCO) with an output power of up to +12.0 dBm, feeding an asymmetric 4 way power divider. A fraction of 0 dBm of the VCO output is driving three I-Q mixers, which realizes a homodyne vector network analyzer. Dual directional couplers were investigated concerning the application for concentration measurements. A wiggly line coupler was separately fabricated and measured as well as implemented in the demonstrator. The entire system is fabricated, calibrated and subsequently characterized with a transmission based permittivity sensor.
elib2cris::1512001600,hofmann2013a